Purification of lysozyme from chicken egg white by high-density cation exchange adsorbents in stirred fluidized bed adsorption system. (1st May 2021) - Show, Pau Loke; Ooi, Chien Wei; Song, Cher Pin; Chai, Wai Siong; Lin, Guan-Ting; Liu, Bing-Lan; Chang, Yu-Kaung
Highlights: Batch and dynamic processes of lysozyme adsorption was comparatively investigated. Two type adsorbents were compared for lysozyme equilibrium and kinetic adsorption. A purification process using SFBA ion exchange chromatography was developed. High recovery yield (94%–100%) and purification factor (26–40 folds) in a single step. Abstract: Lysozyme from crude chicken egg white (CEW) feedstock was successfully purified using a stirred fluidized bed adsorption system ion exchange chromatography where STREAMLINE SP and SP-XL high density adsorbents were selected as the adsorption carrier. The thermodynamic and kinetic studies were carried out to understand the characteristics of lysozyme adsorption by adsorbents under various conditions, including adsorption pH, temperature, lysozyme concentration and salt concentrations. Results showed that SP and SP-XL adsorbents achieved optimum lysozyme adsorption at pH 9 with capacity of ~139.77 and ~251.26 mg/mL, respectively. The optimal conditions obtained from batch studies were directly employed to operate in SFBA process. For SP-XL adsorbent, the recovery yield and purification factor of lysozyme were 93.78% and ~40 folds, respectively. For SP adsorbent, lysozyme can be eluted ~100% with purification factor of ~26 folds. These two adsorbents are highly suitable for use in direct recovery of lysozyme from crude CEW.